2016
DOI: 10.1089/end.2013.0257
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Struvite Stones Using Combined Endourologic and Medical Treatment: Predictors of Unfavorable Clinical Outcome

Abstract: Struvite stones can be managed safely with PCNL followed by medical therapy. The majority of patients with residual fragments demonstrated no evidence of stone growth on medical therapy. With careful follow-up and medical management, kidney function can be maintained and stone morbidity can be minimized. Initial large stone burden, residual stones after surgery, and associated medical comorbidities may have deleterious effect on stone recurrence or residual stone-related events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
14
1
2
Order By: Relevance
“…The ARI found in patients upon initial laboratory testing may have been associated with complete ureteral obstruction or delayed urinary stone treatment. In another study, the rate of post-operative UTI was lower in stone-free patients than in patients with remnant stone (38% vs. 64%) [11]. However in our study, the stone-free rate was not different between the two groups.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The ARI found in patients upon initial laboratory testing may have been associated with complete ureteral obstruction or delayed urinary stone treatment. In another study, the rate of post-operative UTI was lower in stone-free patients than in patients with remnant stone (38% vs. 64%) [11]. However in our study, the stone-free rate was not different between the two groups.…”
Section: Discussioncontrasting
confidence: 85%
“…Kofteridis et al [10] reported that an elderly APN patient with DM showed an increased risk of bacteremia, long hospitalization, and mortality. In another study, it was found that comorbidity factors, such as DM, could influence urinary stone activity and the recurrence of UTI after the treatment of infection and stone [11]. DM, as a comorbidity factor, may be associated with stone activity and UTI recurrence; however, multivariate analysis did not find DM to be an independent risk factor (p=0.150).…”
Section: Discussionmentioning
confidence: 97%
“…Owing to the low incidence of metabolic abnormalities in struvite stone formers and the apparent strong association between struvite stone formation and UTIs, the 2005 American Urological Association (AUA) guidelines on management of staghorn calculi recommended against the metabolic evaluation of pure struvite stone formers 44 . However, studies published after 2005 suggest that metabolic abnormalities occur more frequently in struvite stone formers, including patients with pure struvite stones, than previously reported 45,46 . For instance, a 2017 study by Iqbal et al 45 found metabolic abnormalities in 57% of pure struvite stone formers (from a total of 75 patients), the most common of which were hypercalciuria, hyperoxaluria, hyperuricosuria, and hypocitraturia.…”
Section: Key Pointsmentioning
confidence: 87%
“…Obstructive pyelonephritis, or a kidney stone that has blocked the kidney ducts, is one of the more severe complications of urinary stones, requiring immediate treatment to avoid serious complications such as urosepsis and death [4,7]. Even with stone removal, residual stone fragments may remain in the urinary system, putting these patients at a 40–85% risk for recurrent stones, versus a 0–10% risk for patients who had complete stone removal [8]. …”
Section: Cautis and Urinary Stonesmentioning
confidence: 99%